Belief in a just world, justice concerns, and well-being at Portuguese schools - Correia, I. (2017)
This article investigates the meaning of the belief in a just world (BJW) for justice cognition at school and for subjective well-being. We hypothesized that BJW should serve as a resource helping to maintain positive well-being and to assimilate experienced injustice. The results of two studies with Portuguese school students (7th-12th grade) and one with university students were consistent with our hypotheses. The more the students endorsed the BJW, the more they evaluated their school grades and their teachers' and their peers' behavior towards them as just and the more they were satisfied with life in general. Moreover, the more students felt fairly treated by their teachers, the less they felt distressed at school. Life satisfaction varied however independently of school-specific justice cognitions. This pattern of results persisted when controlled for achievement (grades) as well as for personality dispositions such as self-efficacy, self-esteem, and general trust. The implications of these results for further studies on adolescent development are discussed.